Antimicrobial Activities of Isolated Endophytes from Some Iranian Native Medicinal Plants: Antimicrobial activities some Iranian medicinal plants - Azizollah Ebrahimi; Shirin Asgharian; Saied Habibian (Iranian Journal of Pharmaceutical Sciences, 2010)
Random samples from asymptomatic leaves and branches of five native medicinal plants: Stachys lavandulifolia, Rumex pulcher, Hypericum scabrum, Starja bachteriarica and Achillea kellalensis were collected from Chaharmahal province of Iran and examined for the presence of endophytic bacteria and fungi with biological activity. From 8 isolated endophytic fungi, all displayed considerable activity against at least one indicator fungi. Fungal isolates from R. pulcher leaves and branches showed activity against Aspergillus niger, Penicillium spp, Alternaria spp and S. aureus. Five Bacillus spp strains were isolated from R. pulcher leaves and branches, four (80%) showed activity against S. aureus, and two strains were active against all indicator fungi. Bacillus spp strain isolated from leaves of H.scabrum was active against S. aureus and all 3 indicator fungi. None of the isolated endophytes showed antibacterial activity against E- coli.